Formulasi Susu Pembersih Ekstrak Etanol Herba Pegagan (Centella Asiatica) Menggunakan Surfaktan Tween 80 Dan Span 80 - Nadia Berliana Riwaldi; Mazaya Fadhila (Journal Pharma Saintika, 2023)
Gotu Kola herb is a natural antibiotic that contains the compound asiaticoside which has anti-acne properties in cleansing cosmetics such as cleansing milk. The use of appropriate surfactants can help form cleansing milk preparations. The aim of this research was to see the effect of surfactant concentration on the physical properties of cleansing milk with ethanol extract of gotu kola herb using Tween 80 and Span 80 surfactants. Cleansing milk preparations were made with five formulas with different concentrations of Tween 80 and Span 80, namely 1%, 2%, 3 %, 4 %, and 5 %. The research results showed that the different surfactant concentrations for each formula did not affect the organoleptic, homogeneity, pH and specific gravity of the cleansing milk, but did affect the spreadability of the cleansing milk. The higher the surfactant concentration, the smaller the spreadability of the cleansing milk. All cleansing milk preparations meet SNI characteristics.